A revision of the genus Myroxylon (Leguminosae: Papilionoideae). Issue 4 (December 2015) - Sartori, Ângela; Lewis, Gwilym; Freitas Mansano, Vidal; Azevedo Tozzi, Ana
Summary Myroxylon, an exclusively neotropical legume genus, is taxonomically revised to include two species. Seven lectotypes, one neotype and three synonyms are designated.M. peruiferum andM. balsamum can be differentiated by pellucid dots and streaks in leaflets, adaxial surface dull or shiny, shapes of calyx lobes and standard, size of flowers and the standard petal blade and seed surface. A key to the two species is presented, together with species descriptions, illustrations and comments on the geographical distribution and ecology of each.